Culture methods impact recovery of antibiotic‐resistant Enterococci including Enterococcus cecorum from pre‐ and postharvest chicken. (1st March 2017) - Suyemoto, M.M.; Barnes, H.J.; Borst, L.B.
Abstract: Pathogenic strains of Enterococcus cecorum (EC) expressing multidrug resistance have emerged. In National Antimicrobial Resistance Monitoring System (NARMS) data, EC is rarely recovered from chickens. Two NARMS methodologies (FDA and USDA) were compared with standard culture (SC) techniques for recovery of EC. NARMS methods failed to detect EC in 58 caecal samples, 20 chicken breast or six whole broiler samples. EC was recovered from 1 of 38 (2·6%) and 2 of 38 (5·2%) preharvest spinal lesions (USDA and FDA method, respectively). In contrast, using the SC method, EC was recovered from 44 of 53 (83%) caecal samples, all 38 (100%) spinal lesions, 14 of 20 (70%) chicken breast samples, and all three spinal lesions identified in whole carcasses. Compared with other Enterococcus spp., EC isolates had a higher prevalence of resistance to macrolides. The NARMS methods significantly affected recovery of enterococcal species other than EC. When the postharvest FDA method was applied to preharvest caecal samples, isolates of Enterococcus faecium were preferentially recovered. All 11 E. faecium isolates were multidrug resistant, including resistance to penicillin, daptomycin and linezolid. These findings confirm that current methodologies may not accurately identify the amount and range of antimicrobial resistance of enterococci from chicken sources. Significance and Impact of the Study: Enterococci are an important reservoir for antimicrobial resistance. This study demonstrates how current culture methods underreport resistance to macrolides in enterococci by selecting against strains of Enterococcus cecorum in pre‐ and postharvest chicken. Further, the application of postharvest surveillance methods to preharvest samples resulted in selective recovery of Enterococcus faecium over Enterococcus faecalis . Isolates of E. faecium recovered exhibited multidrug resistance including penicillin, daptomycin and linezolid resistance. These findings suggest that culture methodology significantly impacts the range and amount of antimicrobial resistance detected in enterococci isolated from chicken.